Analisis Kemampuan Menulis (Writing) Ditinjau dari Tingkat Intelegensi Siswa - Puput Zuli Ekorini (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to determine how the impact of students' intelligence levels on writing skills (writing) in English subjects. This research is a case study research with the research subjects of seventh-grade students of one of the Islamic junior high school in Nganjuk Regency with a total of 30 students which are divided into two groups by the researcher they are a group of students with high intelligence scores and students with low intelligence scores. The researcher analyzed the IQ test data conducted by the school several months earlier (less than one year of data accuracy period) and the students' writing test results. The results of the analysis of the data obtained show that students with high intelligence scores on average have good writing skills seen from the five writing aspects used as benchmarks in this study, namely content, organization, grammar, mechanics, and vocabulary. The group of students with high intelligence scores had an average writing score of 85.33 while the group of students with low intelligence scores had an average writing score of 75.07.